Kajian Wawasan Pengetahuan Petani-Tambak Terhadap Perilaku “Silvofishery” Di Pesisir Pantai Timur Kabupaten Sinjai (A Study of Farmer Knowledge on “Silvofishery” Behavior in East Coast of Sinjai District) - Yunus, Budiman (Jurnal Pengelolaan Perairan, 2018)
One of the procedures of coastal ecosystem management is the development of the concept of silvofishery that combines the fishpond with the mangrove vegetation in it. The insight of sivofishery as part of environmental education will contribute to the behavior of farmer rsilvofishery in the coastal ecosystem. Therefore, this research is conducted to determine the effect of 1) environmental insight, ecosystems and conservation, 2) environmental attitudes and 3) environmental motivation, ecosystem and conservation on silvofishery-oriented behaviors. By conducting a survey and questionnaire data obtained from 200 farmers in East Sinjai subdistrict, and with Structural Equation Model (SEM) analysis through Amos 2.2 program, the following research results are obtained; 1) the insight has no direct effect on silvofishery-oriented behavior; 2) attitudes has effect on the behavior of silvofishery insight; 3) insight has no direct effect on motivation; 4) motivation has a direct effect on silvofishery-oriented behavior, especially on embankment and ditch patterns.Keywords: Silvofishery insight and behavior, coastal ecosystem